Colonic Oxidative and Mitochondrial Function in Parkinson’s Disease and Idiopathic REM Sleep Behavior Disorder - C. Morén; Í. González-Casacuberta; J. Navarro-Otano; D. Juárez-Flores; D. Vilas; G. Garrabou; J. C. Milisenda; C. Pont-Sunyer; M. Catalán-García; M. Guitart-Mampel; E. Tobías; F. Cardellach; et al. (Parkinson's Disease)
Objective. To determine potential mitochondrial and oxidative alterations in colon biopsies from idiopathic REM sleep behavior disorder (iRBD) and Parkinson’s disease (PD) subjects. Methods. Colonic biopsies from 7 iRBD subjects, 9 subjects with clinically diagnosed PD, and 9 healthy controls were homogenized in 5% w/v mannitol. Citrate synthase (CS) and complex I (CI) were analyzed spectrophotometrically. Oxidative damage was assessed either by lipid peroxidation, through malondialdehyde and hydroxyalkenal content by spectrophotometry, or through antioxidant enzyme levels of superoxide dismutase-2 (SOD2), glutathione peroxidase-1 (Gpx1), and catalase (CAT) by western blot. The presence of mitochondrial DNA (mtDNA) deletions was assessed by long PCR and electrophoresis. Results. Nonsignificant trends to CI decrease in both iRBD (45.69±18.15; 23% decrease) and PD patients (37.57±12.41; 37% decrease) were found compared to controls (59.51±12.52, p: NS). Lipid peroxidation was maintained among groups (iRBD: 27.46±3.04, PD: 37.2±3.92, and controls: 31.71±3.94; p: NS). Antioxidant enzymes SOD2 (iRBD: 2.30±0.92, PD: 1.48±0.39, and controls: 1.09±0.318) and Gpx1 (iRBD 0.29±0.12, PD: 0.56±0.33, and controls: 0.38±0.16) did not show significant differences between groups. CAT was only detected in 2 controls and 1 iRBD subject. One iRBD patient presented a single mtDNA deletion.